PENANAMAN SIKAP DISIPLIN MODEL BEHAVIORIS, MASIH PERLUKAH? - Maksudi (LPPM STIT Miftahul Ulum Bangkalan, 2019)
Abstract: this paper aims to examine the theory of the importance of behaviorist learning theories in instilling students' disciplinary attitudes. Behaviorist learning theory is often opposed to humanist learning theory which places learners as subjects in education and tends to be free (liberating education). These conditions often cause discipline problems in students and often become conflicts between teachers and students and parents, even in the realm of law. Behaviorist learning theory can be applied in a way that teachers should pay attention to the suitability of behavioristic theories with each learning that will be carried out, not only trapped in the constructivist learning paradigm which is always considered better and traditional models are always lower than modern models and pay attention to human factors and student intelligence, so as not to get stuck in rigid and inhuman patterns. This is needed to open up the human capacity and ability of students to interact with the social environment and prepare to face the realities of life in the future. Keywords: discipline, behavioris Abstrak: tulisan ini bertujuan mengkaji teori pentingnya teori belajar behavioris dalam menanamkan sikap disiplin siswa. Teori belajar behavioris sering dipertentangkan dengan teori belajar humanis yang menempatkan pembelajar sebagai subjek dalam pendidikan dan cenderung bebas (liberating education). Kondisi tersebut sering menimbulkan masalah disiplin pada siswa dan tidak jarang menjadi konflik antara guru dengan siswa dan orang tua, bahkan sampai ke ranah hukum. Teori belajar behavioris dapat diterapkan dengan cara guru hendaknya memerhatikan kesesuaian teori-teori behavioristik dengan tiap pembelajaran yang akan dilaksanakan, tidak hanya terjebak pada paradigma pembelajaran konstruktivisme yang dianggap selalu lebih baik dan model tradisional selalu lebih rendah dari model moderen dan memerhatikan faktor- faktor kemanusiaan dan kecerdasan siswa, sehingga tidak terjebak pada pola-pola yang kaku dan tidak manusiawi. Hal tersebut diperlukan untuk membuka kapasitas kemanusiaan dan kemampuan siswa dalam berinteraksi dengan lingkungan sosial dan bekal dalam menghadapi realitas kehidupan di masa yang akan datang. Katakunci: disiplin, behaviorisme